Triggered Spark Gap Switch with Gas Circulation for Repetitively Operated Multistage Marx Generator; 20th International Symposium on High-Current Electronics (ISHCE) - Yudin A. S. Artem Sergeevich; Martemyanov S. M. Sergey Mikhailovich; Bukharkin A. A. Andrey Andreevich; Bugaev I. V. Igor; Krastelev E. G. Evgeny (2018, 2018)
Title screen